Angka Paling Mungkin (Most Probable Number/MPN) Coliform Sampel Minuman Lidah Buaya Di Pontianak - Elvi Rusmiyanto P.W, Dian Purnama Sari Rahmawati, (Universitas Tanjungpura, 2019)
Aloe vera drink is one of the processed drinks made from the aloe vera leaves, washed until the mucus is reduced and boiled with water. Good drinking water should not contain pathogenic bacteria or organisms that can endanger human health. Coliform is one of the bacteria that can cause disease in humans and is used as an indicator of the presence of pathogenic bacteria. This study aimed to find out the most probable number (MPN) Coliform bacterial in aloe vera drinks which has sold at the location of the sale on Budi Utomo Street, Pontianak City. Sampling used the random sampling method. The MPN test results obtained the lowest MPN/mL index value of 0.091/mL in the samples purchased at the minimarket, while the seven samples obtained at the sales location showed the highest MPN/mL index value of> 24.00/mL. It showed that the eight samples reached over the normal limits listed in SNI 01-3839-1995 based on the Republic of Indonesia Ministry of Health No. 907 / MENKES / SK / VII / 2002 concerning the requirements and supervision of the quality of drinking water which is not more than 0/100 ml.